On the best approximation of classes $W^r H^{ω}$ by algebraic polynomials in the space $L_1$ - Kogan, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain an asymptotic equality for the best approximation of the classes $W^r H^{ω}$ by algebraic polynomials in the space $L_1$ for convex upwards, regularly varying moduli of continuity.